Computational assessment of winglet-induced variations in pressure coefficients on NACA 4418 aircraft wings - Md. Abdullah; Mohammad Zoynal Abedin (Advances in Mechanical Engineering)
This study presents a computational analysis of the effects of winglets on the aerodynamic performance of NACA 4418 aircraft wings, focusing on the variations in pressure coefficients. Using Computational Fluid Dynamics (CFD) simulations, we evaluated the aerodynamic behavior of NACA 4418 wings under various flight conditions. The primary objective was to determine how winglets influence the distribution of pressure across the wing surface, which directly affects lift and drag characteristics. Our simulations utilized a high-fidelity turbulence model to accurately capture the complex flow dynamics near the wing surface. The results indicate a significant modification in the pressure coefficient distribution due to the winglet, particularly at the wing tips with NACA 4418 using the angles of attack (AoA) at 4°, 0°, 4°, 8°, 12°, 16°, 20° and 24° for velocity of 30 m/s, where the reduction in vortex strength leads to decreased induced drag. The results reveal that the pressure coefficient becomes high at 20%C, then decreases to a minimum value at 45%C and then rises gradually up to again a higher value at 80%C for the angles of attack of − 4° and 0° at three airfoil velocity. However, for the angles of attack of 4°, 8°, 12°, 16°, 20° and 24°, the pressure coefficient becomes minimum at 20%C, then gradually increases and finally becomes maximum at 80%C for three airfoil velocities. This is encountered due to the orientation of airfoil’s lower and higher surface. This research provides insights into the design and optimization of winglets for better aerodynamic performance of aircraft wings.